2019
DOI: 10.1002/sim.8370
|View full text |Cite
|
Sign up to set email alerts
|

Two‐stage enrichment clinical trial design with adjustment for misclassification in predictive biomarkers

Abstract: A two‐stage enrichment design is a type of adaptive design, which extends a stratified design with a futility analysis on the marker negative cohort at the first stage, and the second stage can be either a targeted design with only the marker positive stratum, or still the stratified design with both marker strata, depending on the result of the interim futility analysis. In this paper, we consider the situation where the marker assay and the classification rule are possibly subject to error. We derive the seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Misclassification of biomarker is common and needs to be properly adjusted in the clinical study designs. It is shown in Lin et al 18 that biomarker misclassification may have a big impact on type I error and power in the design of clinical studies. As shown in Shih and Lin, 23 stratified design is more efficient than precision medicine design, which is a family of complex biomarker-based-strategy designs discussed in, for instance, Mandrekar and Sargent [24][25][26] and Young et al 27 However, to the best of our knowledge, no stratified study design for survival outcomes, based on predictive biomarkers with an adjustment of misclassification, has been proposed in the statistical literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Misclassification of biomarker is common and needs to be properly adjusted in the clinical study designs. It is shown in Lin et al 18 that biomarker misclassification may have a big impact on type I error and power in the design of clinical studies. As shown in Shih and Lin, 23 stratified design is more efficient than precision medicine design, which is a family of complex biomarker-based-strategy designs discussed in, for instance, Mandrekar and Sargent [24][25][26] and Young et al 27 However, to the best of our knowledge, no stratified study design for survival outcomes, based on predictive biomarkers with an adjustment of misclassification, has been proposed in the statistical literature.…”
Section: Discussionmentioning
confidence: 99%
“…Zang and Guo 17 proposed a two‐stage optimal enrichment design that utilizes the surrogate marker to correct for the biomarker misclassification. Lin et al 18 reported a two‐stage adaptive enrichment design for continuous endpoints, with an adjustment for the misclassification of predictive biomarkers. Those reports focused on the misclassification adjustment for continuous and/or binary endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved through risk algorithms, 23,25,28,29 and imaging or circulating biomarkers with prognostic value. 22,[30][31][32] This approach, however, may affect the generalizability of a trial's findings and does not evaluate whether treatment allocation to specific patient phenotypes aligns with those most likely to benefit. To address this issue, predictive enrichment focuses on the individualized effects of the intervention within the context of a patient's unique phenotypic profile.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved through risk algorithms, 23,25,28,29 and imaging or circulating biomarkers with prognostic value. 22,30,31 A representative example in the cardiovascular field is the use of coronary artery calcium scoring to enrich for individuals at high risk of adverse cardiovascular outcomes. 32 This approach, however, may affect the generalizability of a trial's findings and does not evaluate whether treatment allocation to specific patient phenotypes aligns with those most likely to benefit.…”
Section: Discussionmentioning
confidence: 99%